BAGAIMANA ETIKA KERJA ISLAM MEMPENGARUHI PERSEPSI AUDITOR BERKAITAN FRAUD - Monica Rahardian Ary Helmina; Novita Weningtyas Respati; Ibnu Sutomo (Universitas Lambung Mangkurat, 2021)
The purpose of this study was to examine the effect of Islamic work ethics on perceptions of fraud. This research has an important meaning because it was conducted directly on the government auditors at the Inspectorate of South Kalimantan Province. The questionnaire instrument was used in data collection with the research sample being auditors at the Inspectorate, especially those who were Muslim. Samples were taken as many as 100 respondents for analysis. Linear regression analysis was used to prove the hypothesis. The results showed that Islamic work ethics can influence the perception of fraud in a positive direction